Polyamines methods and protocols - Alcázar, Rubén; Tiburcio, Antonio F. (Methods in Molecular Biology, 2018)
This volume provides readers with a collection of the latest protocols used by researchers to study polyamines (PA). The chapters in this book cover various topics, such as quantification of different polyamines and conjugates, subcellular localization studies, transport, DNA methylation, ODC regulation, genetic and phenotyping analyses, genome-wide association mapping, polyamine applications and cancer. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and cutting-edge, Polyamines: Methods and Protocols is a useful reference for researchers looking to advance and stimulate their knowledge of polyamines